PERTUMBUHAN SEMAI KETAPANG (Terminalia catappa L.) PADA BERBAGAI DOSIS FUNGI MIKORIZA ARBUSKULAR - Lopang, Abigael Indri; Yusran, Yusran; Umar, Husain; Taiyeb, Asgar (Universitas Tadulako, 2020)
Ketapang (Terminalia catappa L.) is one of plant that can grow in critical land like reeds field. Imperata cylindrical (L.) Raeusch is one of plant that can secrete allelopathic substances that is chemicals and it is found on the plants body which is put outside into the environment so it can inhibit or ruin the other plants by using Arbuscular Mycorrhiza Fungi (FMA) as biological fertilizer can increase water absorption and nutrient from the soil. This research used Complete Random Design (CRD) method, and consisted of 4 treatments of arbuscular mycorrhiza fungi that are P0= Without treatment (control), P1= FMA 10g/seedling, P2= FMA 15g/seedling, and P3=FMA 20g/seedling. From the 4 treatment levels, each of them is repeated for ten times, so the total of seedling units that be needed are 4x10=40 (forty) seedling units. The result of this research showed that by giving some dose of arbuscular mycorrhiza fungi type of inoculums consortium by 4 genus (Acaulospora, Gigaspora, Glomus, and Scutellospora), have a real impact toward all the observation parameters that are the high accretion, the diameter accretion, the number of leave accretion, canopy wet weight, root wet weight, crown dry weight, and root dry weight. The treatment dose FMA for 20g (P3) on the polybag gives the mean score of high accretion, diameter, and the biggest number of leave. It show that more and more the high dose of FMA that is applied, than the growth of Ketapang seedling is also getting better because by giving FMA, it can influence the allelophatic substance in the growing media.Keyword: Ketapang, Allelophatic, and Mycorrhiza.